Analysis of the interface characteristics of CVD-grown monolayer MoS2 by noise measurements. (9th March 2017) - Kim, Tae-Young; Song, Younggul; Cho, Kyungjune; Amani, Matin; Ho Ahn, Geun; Kim, Jae-Keun; Pak, Jinsu; Chung, Seungjun; Javey, Ali; Lee, Takhee
Abstract: We investigated the current–voltage and noise characteristics of two-dimensional (2D) monolayer molybdenum disulfide (MoS2 ) synthesized by chemical vapor deposition (CVD). A large number of trap states were produced during the CVD process of synthesizing MoS2, resulting in a disordered monolayer MoS2 system. The interface trap density between CVD-grown MoS2 and silicon dioxide was extracted from the McWhorter surface noise model. Notably, generation–recombination noise which is attributed to charge trap states was observed at the low carrier density regime. The relation between the temperature and resistance following the power law of a 2D inverted-random void model supports the idea that disordered CVD-grown monolayer MoS2 can be analyzed using a percolation theory. This study can offer a viewpoint to interpret synthesized low-dimensional materials as highly disordered systems.